Daughters Who Walk This Path - Kilanko, Yejide (Nigeria, 2012)
Daughters Who Walk This Path depicts the dramatic coming of age of Morayo, a spirited and intelligent girl growing up in 1980s Ibadan who is thrust into a web of oppressive silence woven by the adults around her. It's a legacy of silence many women in Morayo's family share. Only Aunty Morenike-once protected by her own mother-provides Morayo with a safe home, and a sense of female community which sustains Morayo as she grows into a young woman in bustling, politically charged, often violent Nigeria.
Keywords: Fiction